Design and modeling uninterrupted power system with IEC 61850-7-420 - Sung Lim, Hyun; Ho Ryu, In; Ho Bang, Jun (International Journal of Engineering and Technology, 2018)
Background/Objectives: Micro-grid is new electrical networks with Distributed Energy Resources(DERs) like photovoltaic, energy storage, small generator. IEC 61850 is international standard of integrated power system with various DERs.Methods/Statistical analysis: Many researches are being conducted about modeling Distributed Energy Resource and designing system operation and protection method. So, we need integrated system modeling with IEC 61850-7-420 and design uninterrupted system with Photovoltaic, Energy Storage System, Generator.Findings: To operate DERs with uninterrupted system, it required electrical facility like Closed Transition Transfer Switch (CTTS). CTTS performs an uninterrupted switching operation between two power sources. International Electrical Code 61850-7-420 described some DERs model and LNs (logical nodes) and data classes. This logical nodes and data classes are effective in modeling DERs. So, this paper describes uninterrupted system for mapped IEC 61850 and considers LNs in existence and new logical nodes.Improvements/Applications: The proposed uninterrupted systems combined the DERs with IEC 61850 and the systems are applicable to Micro-grid systemÂ Â